The minimum clinically important difference: which direction to take. (25th March 2019) - Draak, T. H. P.; de Greef, B. T. A.; Faber, C. G.; Merkies, I. S. J.; ,
Abstract : Over the past decades in modern medicine, there has been a shift from statistical significance to clinical relevance when it comes to interpreting results from clinical trials. A concept that is increasingly being used as a surrogate for clinical relevance and effect size calculation is the minimum clinically important difference (MCID). In this paper, an overview is presented of the most important aspects of the MCID concept used in research trials and a discussion of what this means for the neurological patient in clinical trials and daily practice is given. Is the MCID the best outcome measure cut‐off to be implemented?